A novel method for identifying surface waves in periodic structures. Issue 98 (July 2017) - Pu, Xingbo; Shi, Zhifei
Abstract: In this study, the propagation of surface waves in both one- and two-dimensional periodic structures is investigated. By combining finite element method, an energy distribution parameter is defined and a new method for identifying surface wave modes is suggested. The effectiveness of this new method is validated by comparing with some related studies. Furthermore, this method is used to study a two-dimensional periodic pile-soil system based on a three-dimensional numerical model and the dispersion curves of surface waves are easily obtained. To show the efficiency of attenuation zone, the responses of a finite periodic pile-soil system to a surface wave input are simulated. Results demonstrate that the region of excitation frequency in which vibration reduction occurs is fully consistent with the theoretical attenuation zone for surface waves. The advantage of this method is that it makes the study of surface waves more convenient and accurate. Highlights: An energy distribution parameter is defined. A new method for identifying surface wave modes is suggested. The effectiveness of this new method is validated. This method makes the study of surface waves more convenient and accurate.